2020
DOI: 10.1186/s40658-020-00341-8
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study on using 252Cf for the treatment of esophagus tumor in human phantom

Abstract: Due to the sensitivity of this tissue, and the potential for metastasis of its cancer as well, finding accurate methods to be employed for the treatment of esophagus tumors is of especial interest for the researchers. The present study deals with a Monte Carlo simulation of 252Cf neutron brachytherapy for treating these tumors using MCNPX (Version 2.6.0) code. The widely accepted AAPM TG-43 protocol has been used to benchmark the simulated source and to examine the accuracy of the modeling. The MIRD human phan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Note that the RBE and ̅ Q are sensitive to neutron energy and greater than unity whereas for photons, value of these parameters is unity, independent of photon energy (Karimi-Shahri et al 2021). Rasouli et al (2020) demonstrated that the contribution of neutrons to the total dose is maximum and the equivalent gamma dose is negligible when compared to those of neutrons. The above findings showed that in terms of RBE-weighted dose or equivalent gamma dose, relative contribution from neutrons is maximum as compared to photons.…”
Section: Cf Brachytherapy Source and Phantom Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that the RBE and ̅ Q are sensitive to neutron energy and greater than unity whereas for photons, value of these parameters is unity, independent of photon energy (Karimi-Shahri et al 2021). Rasouli et al (2020) demonstrated that the contribution of neutrons to the total dose is maximum and the equivalent gamma dose is negligible when compared to those of neutrons. The above findings showed that in terms of RBE-weighted dose or equivalent gamma dose, relative contribution from neutrons is maximum as compared to photons.…”
Section: Cf Brachytherapy Source and Phantom Modelsmentioning
confidence: 99%
“…Hence, the present study considers only the neutron components of 252 Cf. In the Monte Carlo calculations, the neutron energy spectrum of a 252 Cf source was modeled as a Watt fission spectrum (Brown et al 2002, Rasouli et al 2020, and it is given by the equation:…”
Section: Cf Brachytherapy Source and Phantom Modelsmentioning
confidence: 99%
See 2 more Smart Citations